Standar Operasional Produk Pembiayaan dalam Akad Murabahah pada Bank Muamalat - Indrawati, Peni (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2023)
The Islamic banking system is a system of the real sector of a country's economy that operates based on Islamic sharia principles which are identical to profit sharing. Meanwhile, the purpose of this study is to identify and describe the form of the contract and operational standards of murabahah financing products and to analyze the application of sharia principles in murabahah financing contracts at Bank Muamalat Surabaya. The results showed that: (1) The form of contract and operational standards of murabahah financing products at the Darmo branch of Muamalat bank with reference to the provisions of the Sharia Banking Law, BI (Bank Indonesia), OJK (Financial Services Authority) and DSN-MUI Fatwa still exist. Some things that need to be considered are the principles of transparency and openness in order to avoid asymmetric information in murabahah transactions. (2) The application of sharia principles in the murabahah financing contract at the Darmo branch of the Muamalat bank is in accordance with the Sharia Banking Law and the Fatwa of the DSN-MUI, where financing is based on Islamic principles, that is, does not contain elements of usury, maisir, garar, haram, and unjust . This prohibition is in line with maqasid sharia in order to prevent harm (daf'ul-mafasid), bring benefit (jalbul-maslahah), and maintain five basic things namely religion, soul, mind, lineage, and property.